Analysis of Patent Production in Peruvian Universities - Karen Esteincin, Cuba Vargas; Vanessa Yaniz, Palomino Monteza; PUCUHUAYLA REVATTA, Félix Rogelio; Rivaldo Carlos, Duran Aquino (LACCEI, 2025)
Universities play a crucial role in generating knowledge and innovation, with a focus on training professionals capable of addressing social issues. This is why, in Latin America, universities have increased patent production, although they still face obstacles in technology transfer. Programs like CATI in Peru have driven innovation, promoting collaboration with industry and enhancing the economic sustainability of institutions. Patents reflect the research capacity and global impact of universities, being key to attracting funding and collaborations, which is why the number of patent applications in Peru has significantly increased, with the National University of Engineering and the Private University of the North standing out as leaders in this field.